Pendampingan Analisis Usaha Budidaya Air Tawar Melalui Sistem Polikultur di Kecamatan Nunukan Selatan - Sinaga, Samuel Partogi Hasudungan; Samsidar Samsidar; Nasrudin, Abdul Rohman; Ilham Ilham; Alamsyah, Misdar; Ananda, Yosep Yuswanto Tri (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
This community service initiative provides a comprehensive business analysis to evaluate financial feasibility, aiming to mitigate potential losses and ensure operational viability. By offering concrete data on business prospects and challenges, this analysis serves as a strategic guide for resource allocation and market targeting, while simultaneously enhancing attractiveness to potential investors. The program was conducted in the South Nunukan District, Nunukan Regency, North Kalimantan. As Indonesia's 34th province and a strategic border region, North Kalimantan faces significant challenges in food security due to limited supply chains. A central component of this study is the Break-Even Point (BEP) analysis—the threshold at which a business incurs neither profit nor loss. The BEP analysis provides critical insights into the relationship between pricing, operational costs, sales volume, and production levels. Consequently, it serves as a vital decision-making tool for business owners to optimize profitability. The results of this study demonstrate that, despite the continued use of traditional methods, the polyculture system remains highly profitable and sustainable for the local community.